“Don’t Mention the War”: Live Aid Concert and UEFA EURO 2020 Finals as Examples of the Separation of Global Mega-events from Political Conflict - Bridgman, Timothy (Analyses/Rereadings/Theories: A Journal Devoted to Literature, Film and Theatre, 2023)
This research compares two important British live entertainment mega-events held at Wembley Stadium in London, and examines their attempts to distance themselves from the mentioning of political conflict or war. The paper will argue that the Live Aid concert in 1985 and UEFA EURO 2020 final, held in 2021, despite being separated by thirty-six years, share many common features which, in turn, determined their approach to social responsibility. The paper will support this claim by explaining the two events’ official social responsibility programs and providing examples of performer activism occurring within a small window left open for independent free speech. It will conclude that despite the prominence allocated to addressing social issues at both events, anti-political conceptualisation prevailed, resulting in the avoidance of all mentioning of political conflict and war. It proposes that it is only through the analysis of activism that it becomes possible to understand the complexity of the political realities surrounding a major live music or sporting event.